Synthesis of 2,5-bis-(4’-hydroxybenzylidene) cyclopentanone and 2,5-bis-(4’-chlorobenzylidene) cyclopentanone compounds and antiproliferative tests to HeLa cells - ., Pudjono; ., Sismindari; Widada, Hari (Indonesian Journal of Pharmacy, 2008)
2,5- bis - ( 4’-hydroxy-3’- methoxybenzylidene ) cyclopentanone com- pound was know have cytotoxic activity to Mieloma , Raji and HeLa cells better than curcumin. In effort to discovered new compound which have cytotoxic activity, it necessery to modify this compound by changing some group on it with lossing methoxy group, so was yielded two compounds, there were 2,5- bis - ( 4’-hydroxy benzylidene) cyclopentanone and 2,5-bis – ( 4-chlorobenzylidene ) cyclopentanone. The synthesis was done by reaction between 4-hydroxyand 4-chlorobenzaldehydes and cyclopentanone through Claisen-Schmidt condensation reaction catalyzed by sulfuric acid with methanol and 2-butanol as solven. The structure of product was characterized by spectra of Infrared and Massspectroscopy, then anti proliferation activity to HeLa cells counted base on IC50 values The results showed that 2,5- bis -(4’-hydroxy benzylidene) cyclopentanone (IC50 value : 0.656 mM) have higher toxicity than 2,5- bis -(4’-chlorobenzylidene) cyclopentanone (IC50value : 5.376 mM).Key words : Claisen-Schmidt condensation; 2,5- bis -(4’-hydroxy benzylidene) cyclopentanone; 2,5- bis -(4’-chloro-benzylidene) cyclopentanone; anti proliferative; HeLa cell.